Analysis of the health level of banks using RGEC method (Risk Profile, Good Corporate Governance, Earning, Capital) on private public banks registered in the Indonesia Stock Exchange in 2020-2022 - Zulaifah; Wahyuni; Ismawati (IECON, 2024)
This research aims to determine the health level of private commercial banks listed on the Indonesian stock exchange for the 2020-2022 time period using the RGEC method in terms of risk profile, good corporate governance, earnings and capital factors. The population used in the research was 10 private banks listed on the Indonesian stock exchange. This type of research is research using a quantitative descriptive approach method. The ratios used in assessing bank health include risk profile using 2 ratios, namely NPL and LDR, GCG factors using self-assessment, Earnings using 2 ratios, namely ROA and NIM, and capital factors using the CAR ratio. The research results show that the health level of private commercial banks from 2020 to 2022 is categorized as "healthy". In this case, private commercial banks are considered capable of improving corporate health from the aspects of credit policy, liquidity, profits and capital and banks are able to maintain customer trust.